Does the trade structure among the league of Arab states show potential for a successful regional economic integration? - Hamid, Zarinah; Mohd Amin, Ruzita; Md Saad, Norma (SESRIC, 2008)
The League of Arab States (LAS) has placed an equally important attention on economic matters whereby the Economic and Social Council of the League adopted resolution No. 1317 of the 1980 Amman Summit declaring the establishment of a Pan-Arab Free Trade Area. This paper investigates whether or not the LAS possesses the necessary prerequisites for a successful regional trade arrangement. It examines the trade structure among five LAS members, namely Egypt, Jordan, Saudi Arabia, Syria and Oman by analyzing their dynamic exports as well as their “trade concentration”, and “trade divergence” profiles between the years 1990 and 2003. In general, the findings indicate that the existing trade structure may not facilitate intra-regional trade among LAS members. Divergence estimates indicate that only Jordan shows prospects for greater regional exports while the prospects for Egypt, Oman, Saudi Arabia and Syria do not appear to be encouraging. Except for Jordan, exports are found to be highly concentrated especially for Saudi Arabia and Syria. Therefore, based on the findings there is a need for these countries to realign their trade policies in order to promote a more favorable environment for the creation of the Pan-Arab Free Trade Area.